Firms in International Trade: Trade Policy Implications of the New New Trade Theory. Issue 2 (1st December 2014) - Ciuriak, Dan; Lapham, Beverly; Wolfe, Robert; Collins‐Williams, Terry; Curtis, John
Abstract: This paper explores the implications of recent developments in firm‐based trade theory and empirics for trade policy and negotiations. While traditional trade theory focused on the country, and the new trade theory of the 1980s adopted the industry as the unit for analysis, the newest theory emphasizes the role of firms and firm heterogeneity in international trade. We describe insights from this reformulation of theory and the empirical literature that illuminates it. The realities of trade as now understood show the need for a new new trade policy. Evaluating trade at the level of the firm implies that overcoming firm‐level fixed costs of trade and reducing uncertainty lead to increased trade along margins that generate the highest productivity, innovation and welfare gains. The traditional market access agenda ought now to be less important on the multilateral agenda than services, standards, trade facilitation, procurement and innovation policy. The analytical needs of a new new trade policy require new models and more access to firm‐level data to formulate and evaluate the multifaceted impacts of trade policy. Abstract : In addition to the effects on existing trade flows, trade negotiators should evaluate the impact of policy on the potential expansion of trade in products that previously were not traded, the diversification of exported products into new markets, and the entry of new trading firms.